(untitled) (Research, Society and Development, 2020)
Facing an alarming increase in failures, which, over the years, has been recorded due to the way in which mathematical knowledge has been transmitted to students, new methodological alternatives have been inserted in the school context, among them, the inclusion of ludic activities. This it article aims to identify the acquired knowledge through of a geometric mathematical game made with recyclable materials built linking Mathematics to Physical Education connecting awareness with environmental issues. After a theoretical analysis on the view of teaching Mathematics by different researchers, we report the methodological actions and perceptions after the application of the game. The results indicate that the inclusion of recyclable twister mobilized students of an eighth year of elementary school to have mathematical knowledge through playfulness, linking logical reasoning to body balance. The recognition of geometric figures in the way that was proposed by the activity developed, brought to the students the idea of ​​a Mathematics that is accessible to all, in an equal way.The proposed game combined Mathematics with perceptions to sustainability.